'I don't like this job in my front room': Practising probation in the COVID-19 pandemic. (December 2021) - Phillips, Jake; Westaby, Chalen; Ainslie, Sam; Fowler, Andrew
The Exceptional Delivery Model for probation practice in England and Wales meant that probation practitioners predominantly worked from home during the COVID-19 pandemic, engaging and supervising service-users remotely. This article explores the impact of the Exceptional Delivery Model on staff and their practice. We begin by considering how probation practice changed because of the implementation of the Exceptional Delivery Model and the impact that this has had on probation staff. The reality of probation work is brought into perspective when there are children in the home and the demarcation of work and home life is easily blurred, especially when considered through the lens of 'emotional dirty work'. We then present analysis of interviews with 61 practitioners and managers in the National Probation Service. The interviews were primarily focused on staff wellbeing and emotional labour as opposed to the impact of the pandemic, but participants regularly raised the pandemic in discussions. We focus on three key themes: the challenges of working from home and remote communication, experiences of managing risk through doorstep visits and the spill over of probation work into personal lives. The article concludes by considering what the findings tell us about probation work and potential future implications.